Spectroscopic analysis of plastic adulterated cooking oil- a preliminary test - Yusof, Nurnajwa Mohamed (Universiti Sains Malaysia, 2016)
Expensive edible oil for examples virgin olive oil (VOO) and extra virgin olive oil (EVOO) are commonly adulterated with cheap edible oil for examples peanut oil and palm oil. The main purpose of such an adulteration is for profiteering. Although such an adulteration does not have a direct impact on the consumer’s health, it affects the order of the economy. More sinister and of potential hazard to the consumer’s health is the adulteration of edible oil with inedible materials or compounds for example inedible plastic for instances low-density polyethylene (LDPE), high density polyethylene (HDPE) and polypropylene (Achillas et al.) use in carrier bag, plastic packaging and also plastic straws. It has been reported that some irresponsible street hawkers selling banana fritters, fish fritters and fried chicken, mixed their cooking oil with inedible plastic prior to cooking so as to make their fried foods produce crispier for a longer period of time. The primary objective of this project was to detect the presence of inedible plastic in edible cooking oil using ATR-FTIR spectrometer and chemometrics techniques of Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA). Six bottles of Neptune® cooking oils purchased from a convenience store within the Kubang Kerian, Kelantan area were adulterated with transparent plastic bags at high temperature. Upon cooling to room temperature, the plastic adulterated cooking oils (PLS) together with their fresh counterparts i.e. unused cooking oils (UCO) were analysed using the ATR-FTIR and their FTIR spectra (within the fingerprint region) were subjected to PCA. Distinctive groupings of plastic adulterated cooking oil (PLS) and unused cooking oils (UCO) suggested that PLS can be differentiated with UCO using chemometrics techniques of PCA and HCA which also indicates the potential used of ATR-FTIR coupled with chemometrics techniques for monitoring edible oil adulterated with inedible plastic.